2015
DOI: 10.1155/2015/186927
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Prevalence of Eating Disorders in Obsessive-Compulsive Disorder and Other Anxiety Disorders

Abstract: Objective. The purpose of this study was to compare the prevalence of comorbid eating disorders in Obsessive-Compulsive Disorder (OCD) and other common anxiety disorders. Method. 179 patients from the same geographical area with a diagnosis of OCD or an anxiety disorder were divided into two groups based on their primary diagnosis. The prevalence of a comorbid eating disorder was calculated in both groups. Results. There was no statistically significant difference in the prevalence of comorbid eating disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
2
8
0
1
Order By: Relevance
“…These patients may have a clinical ED or be at high risk of developing one, and may be in need of ED-specific treatment at some point. A previous study found that 18-34% (depending on cut-off score) of female patients with OCD screened positive for an ED [18], and another that 7% of female patients had a co-occurring ED [14]. Although these studies used ED measures other than the EDE-Q, their rates are comparable to the ones we report.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These patients may have a clinical ED or be at high risk of developing one, and may be in need of ED-specific treatment at some point. A previous study found that 18-34% (depending on cut-off score) of female patients with OCD screened positive for an ED [18], and another that 7% of female patients had a co-occurring ED [14]. Although these studies used ED measures other than the EDE-Q, their rates are comparable to the ones we report.…”
Section: Discussionsupporting
confidence: 81%
“…Available studies have estimated that between 3 and 13% of patients has a lifetime history of an ED [13][14][15][16][17]. Lifetime ED rates are higher among female compared to male patients [14,16,18]. Less is known about how many patients with OCD have a current comorbid ED, but estimates range between 1 and 10% [13,14,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations